Legal Challenges in Regulating and Supervising Street Vendors in Banten Province - Hudjolly; Yana Priyana (West Science Law and Human Rights, 2023)
In Banten Province, Indonesia, street vending is a prominent and vibrant economic activity that boosts local economies and the region's cultural diversity. Nonetheless, there are particular legal difficulties with regard to street vending oversight and control. This study examines the perspectives and experiences of street vendors, looks into the legal ramifications of street vending in Banten Province, and considers the wider implications for community well-being and government. The results show a complicated regulatory environment with conflicting laws, uneven enforcement, and unclear provisions. Street sellers routinely run afoul of the law, struggle to get licenses, and have run-ins with the law, all of which contribute to their financial instability. Inadequate enforcement, corruption, and rent-seeking conduct are examples of regulatory issues that disproportionately affect vulnerable communities. Comparative analyses provide information from globally effective techniques. Simplifying licensing processes, boosting public awareness campaigns, strengthening enforcement strategies, and encouraging participatory regulation are among the recommendations. It is also suggested to create zones specifically for vending. The objective of these proposals is to create a balanced environment that is advantageous to both street sellers and the larger community by creating a more equitable and effective regulatory framework for street vending in Banten Province.